2014
DOI: 10.5098/fhp.5.4
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-Hydrodynamic Behavior of Methanol Charged Closed Loop Pulsating Heat Pipe

Abstract: Flow visualization experiment has conducted on the methanol charged vertical Closed Loop Pulsating Heat Pipe (PHP) to investigate the effect of different heat inputs on overall thermal resistance, average evaporator and condenser temperature and corresponding hydrodynamic behavior. A PHP has made from four parallel glass tubes forming adiabatic section, interconnected alternately by copper U tubes, having internal and external diameter 2 mm and 3.06 mm respectively. The length of evaporator, condenser and adia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 10 publications
1
8
0
2
Order By: Relevance
“…In the first part of this paper, Borkar and Pachghare (2014) conclude that, the thermal performance of device increases with increasing heat input. With increasing heat input, the evaporator temperature rises, resulting in a greater density gradient in the tubes, simultaneously the liquid viscosity also drops, that diminishing the wall friction and evaporation rate of working fluid inside the loop.…”
Section: Thermo-hydrodynamic Behavior Of Phpmentioning
confidence: 99%
“…In the first part of this paper, Borkar and Pachghare (2014) conclude that, the thermal performance of device increases with increasing heat input. With increasing heat input, the evaporator temperature rises, resulting in a greater density gradient in the tubes, simultaneously the liquid viscosity also drops, that diminishing the wall friction and evaporation rate of working fluid inside the loop.…”
Section: Thermo-hydrodynamic Behavior Of Phpmentioning
confidence: 99%
“…However, this benefit does not have much effect on the working fluid movement and heat transfer capability. At start-up, the working fluid regime is generally in the form of slug flow (Borkar & Pachghare, 2014). Thus, the effect of gravitational potential is much more dominant than other patterns, such as annular/semi annular patterns.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…One of the methods to evaluate OHP characteristics and performance is by observing the oscillation temperature of the evaporator, adiabatic and condenser. The observations of temperature evolution were analyzed and associated with visualization studies by previous researchers [2,9,12,15,20]. When heat was applied on the evaporator section, the evaporator temperature (T4) and adiabatic (T2 and T8) immediately increased with different degrees of slope (shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…An experimental study by Saha et al [10] showed that methanol and water should be the first consideration when choosing a working fluid for open loop OHP with vertical and horizontal orientation. Several visual studies have been conducted by various researchers that successfully characterized at least five different flow patterns [2,9,[11][12][13][14][15][16]. The results were dispersed bubble, vapor plug, long vapor plug, semi-annular flow and annular flow.…”
Section: Related Researchmentioning
confidence: 99%
See 1 more Smart Citation